The Use of Leuprolide Acetate in the Management of High-Risk Sex Offenders. (December 2019) - Gallo, Alessandra; Abracen, Jeffrey; Looman, Jan; Jeglic, Elizabeth; Dickey, Robert
The present study investigates whether leuprolide acetate (Lupron) adds to the efficacy of traditional sex offender treatment. A group of sex offenders receiving both Lupron and cognitive behavioral therapy (CBT; n = 25) were compared with a group of sex offenders receiving only CBT ( n = 22). Treated subjects were compared with norms available with reference to the Static-99R, as well as compared with a sample of untreated, nonsexual violent offenders ( n = 81), to provide baseline data regarding risk of violent recidivism. Results indicated that subjects receiving Lupron were at significantly higher risk of recidivism and significantly more likely to be diagnosed with a paraphilia than subjects receiving only CBT, a priori. Both treated groups of sexual offenders recidivated at substantially lower rates than predicted by the Static-99R. Currently, this study represents the only, long-term outcome study on Lupron administration using officially recorded recidivism as the primary dependent measure.